2014
DOI: 10.1080/13548506.2014.902483
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study examining mindfulness-based cognitive therapy in psoriasis

Abstract: A sub-population of people with psoriasis have strong causal beliefs about stress, high levels of emotional distress (anxiety and depression) and an impaired quality of life (QoL). Mindfulness-based cognitive therapy has been found to reduce levels of stress and distress and to improve QoL. This pilot study in people with psoriasis aimed to test the hypothesis that mindfulness could reduce stress and thereby lessen psoriasis severity, improve QoL and reduce distress. Twenty-nine people with psoriasis (22-70-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 22 publications
1
82
2
4
Order By: Relevance
“…Several studies have reported the improvement in skin symptoms following the initiation of SSRI treatment . Nonpharmacological treatments have been associated, such as relaxation, a method teaching how to reduce muscle tone, and meditation . Meditation is reported to reduce by 30–35% the predefined time required to obtain a clinical response to PUVA therapy or UVB phototherapy .…”
Section: Stress Management During Psoriasismentioning
confidence: 99%
“…Several studies have reported the improvement in skin symptoms following the initiation of SSRI treatment . Nonpharmacological treatments have been associated, such as relaxation, a method teaching how to reduce muscle tone, and meditation . Meditation is reported to reduce by 30–35% the predefined time required to obtain a clinical response to PUVA therapy or UVB phototherapy .…”
Section: Stress Management During Psoriasismentioning
confidence: 99%
“…In adults with eczema, psychotherapy aimed at helping patients to identify and constructively deal with life stresses has also shown benefit for decreasing disease severity when used as an adjunct to standard treatment 60. Similar findings have been observed in patients with psoriasis, where supplemental psychotherapeutic interventions have resulted not only in improvements in HRQoL scores and subjective measures of anxiety/depression but also in reductions in psoriasis severity 61,62…”
Section: Treatmentmentioning
confidence: 64%
“…In fact in two studies done by Gupta et al [18,19], an increase in stress and depressive symptoms were found to have a significant statistical correlation with an increase in psoriasis flare-ups and pruritus severity along with a more clinically disfiguring disease. In addition, studies have shown that a decrease in depression/depressive symptoms due to medication or therapy is associated with a decrease in psoriasis severity and vice versa [20,21,22,23,24,25,26]. The question now remains: is this correlation merely due to the negative psychological effects inherent in any clearly discernible skin disorder, or any disorder in general, such as social anxiety, low self-esteem, shame/embarrassment etc., or is there an underlying pathophysiological mechanism involved?…”
Section: Depression and Psoriasis: A Psychodermatological Associationmentioning
confidence: 99%